(untitled) (Mustansiria Dental Journal, 2019)
Background: Thermosense material is the innovative virtually unbreakable, new monomer free rigid denture base material easy and quick to polish and available in 10 colors, suitable to patients unable to accept denture made from materials that could result in allergic reactions or other sensitivity problems. This type is suitable for full and partial denture and can be used for rebase and reline jobs. Also suitable for overdenture on implant and for repair. Material and methods: sixty samples were prepared and divided in to two main groups according to the type of material that used (thermosense denture base material and heat cure acrylic denture base material). Each main group were subdivided in to three subgroups according to the type of test that has used (Hardness, impact strength, and transverse strength). Data were analyzed by oneway analysis of t-test. Results: for this study the result for three tests; hardness, transverse strength and impact strength show high significant difference. conclusion: This study showed Thermosense denture base material had higher impact strength than Heat cure acrylic denture base material but this material had higher transverse strength and hardness than Thermosense denture base material.